2013
DOI: 10.1111/liv.12140
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability as a contributor to thrombotic complications in the liver transplant recipient

Abstract: Traditionally, perioperative bleeding complications were a major concern during orthotopic liver transplantation, but a tremendous decline in transfusion requirements has been reported over the last decade. In recent years, there has been an increasing awareness towards perioperative thrombotic complications, including liver vessel thrombosis, and systemic venous and arterial thromboembolic events. Whereas a number of these thrombotic complications were previously categorized as surgical complications, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 65 publications
4
73
0
1
Order By: Relevance
“…It has been demonstrated that patients frequently become pro-thrombotic during the perioperative period [49] . This typifies the challenges of haemostatic management during LT since inappropriate correction of a transient coagulopathy could lead to excess thrombotic complications, including hepatic artery thrombosis [50] .…”
Section: Donohue CI Et Al Reducing Transfusion Requirements In Livementioning
confidence: 99%
“…It has been demonstrated that patients frequently become pro-thrombotic during the perioperative period [49] . This typifies the challenges of haemostatic management during LT since inappropriate correction of a transient coagulopathy could lead to excess thrombotic complications, including hepatic artery thrombosis [50] .…”
Section: Donohue CI Et Al Reducing Transfusion Requirements In Livementioning
confidence: 99%
“…18 Also, most pertinently, thromboembolic events are associated with a hypercoagulable state. 19,20 A great many 'risk' factors (including both genetic [21][22][23][24][25][26][27][28] and environmental or 'lifestyle', as well as those accompanying medical interventions [29][30][31][32] ) can contribute to this hypercoagulability, [33][34][35][36][37][38] and understanding these ( Fig. 1) and how they interact probably makes this a problem that is thus best considered using the tools and ideas (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the sample preparation and assays are provided in Appendix 1. The protein C/factor VIII ratio was calculated as a surrogate marker of anticoagulant and procoagulant balance [25,26]. Thrombin generation was assessed on plateletpoor plasma using the calibrated automated thrombography method as described by Hemker et al [27].…”
mentioning
confidence: 99%